Analysis of Marketing Strategy as Recovery Effort in Alamendah Village During the COVID-19 Pandemic - Yuliana, Rinrin; Waluya, Bagja; Fitriyani, Endah (Journal of Tourism Education, 2022)
The COVID-19 pandemic has affected several industries, one of which is the tourism industry such as hotels, restaurants, retailers and various tourist attractions in Indonesia being closed due to this pandemic. One of the affected tourist attractions is the Alamendah Tourism Village, which is located in Bandung Regency, West Java. This study aims to determine the marketing strategy as a recovery effort in the Alamendah Tourism Village during the COVID-19 pandemic. The marketing strategy carried out in this study is from the 7P aspect in the marketing mix, namely Product, Place, Promotion, Price, People, Physical Evidence, and Process. This study uses a qualitative approach with descriptive analysis methods, the resource persons in this study consisted of the managers of the Alamendah Tourism Village, the Bandung Regency Culture and Tourism Office and Tourists. The results of this study indicate that the marketing strategy carried out by the Alamendah Tourism Village before and during this pandemic had positive changes, which initially only depended on offline marketing to become online and added new tour packages, namely Virtual Tours.